INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN MULTILINGUAL EDUCATION - Sh. D. Bakhriyeva (Web of Journals Publishing, 2024)
This article discusses the use of innovative pedagogical technologies in multilingual education, draws attention to the importance of using new pedagogical approaches and tools for effective learning in a multilingual environment. The article explores various innovative pedagogical techniques such as computer programs, interactive textbooks, online resources and others that help develop students' skills and knowledge in several languages. Based on the conducted research and practical experience, the article offers recommendations and practical recommendations for the successful implementation of innovative pedagogical technologies in a multilingual educational environment. The advantages and disadvantages of using innovative pedagogical technologies in multilingual education are noted. In addition, the article suggests ways to use innovative pedagogical technologies in teaching Russian as a foreign language. This article is of interest to educators, researchers and all interested parties seeking to improve the quality of education in a multilingual environment and introduce innovative approaches to the educational process.
Keywords: pedagogical innovation, multilingual education, the main vectors of the development of multilingual education, Russian as a foreign language, communicative method, computer-oriented learning technology, innovative methods of working with multimedia resources, individualization of learning.